1982
DOI: 10.1590/1809-43921982122333
|View full text |Cite
|
Sign up to set email alerts
|

Balanço hídrico de pequena bacia hidrográfica em floresta amazônica de terra firme

Abstract: Resumo Estimaram-se as taxas anuais de transpiração, evapotranspiração e escoamento superficial de uma bacia hidrográfica de 1,3 km2, localizada na Reserva Ducke, a 26 km de Manaus. Através dos resultados, observou-se que, do total da precipitação ocorrida, cerca de 62% são transpirados e 80,7% evapotranspirados, enquanto que o escoamento superficial foi representado por uma parcela de 19,3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

1987
1987
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 1 publication
0
8
0
7
Order By: Relevance
“…They concluded that the annual evapotranspiration obtained by their study was almost as same as the potential evapotranspiration calculated by the Penman method using the data of Manaus from 1931to 1960(Villa Nova et al, 1976 and their results might be right. However, since the annual evapotranspiration at Barro Blanco (See Table 4) was estimated to be more than the annual potential evapotranspiration, runoff might be underestimated in their study as well as the case of Leopoldo et al (1982). However, these results may represent the characteristics of the hydrological cycle near Manaus, since Shuttleworth (1988) also concluded that the annual evapotranspiration, based on a direct measurement, was almost as same as the annual potential evapotranspiration calculated by the Penman method and as the Priestley-Taylor annual potential evaporation (Priestley and Taylor, 1972).…”
Section: Comparison With Previous Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…They concluded that the annual evapotranspiration obtained by their study was almost as same as the potential evapotranspiration calculated by the Penman method using the data of Manaus from 1931to 1960(Villa Nova et al, 1976 and their results might be right. However, since the annual evapotranspiration at Barro Blanco (See Table 4) was estimated to be more than the annual potential evapotranspiration, runoff might be underestimated in their study as well as the case of Leopoldo et al (1982). However, these results may represent the characteristics of the hydrological cycle near Manaus, since Shuttleworth (1988) also concluded that the annual evapotranspiration, based on a direct measurement, was almost as same as the annual potential evapotranspiration calculated by the Penman method and as the Priestley-Taylor annual potential evaporation (Priestley and Taylor, 1972).…”
Section: Comparison With Previous Studiesmentioning
confidence: 94%
“…For example, the result of Leopoldo et al (1982) is about 80 percent. This is because of the underestimation of the annual runoff, since the discharge measurement instrument was destroyed by flood in the course of their experiment.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the small dataset, the species-specific conductive xylem area scaled relatively well with the diameter at breast height of a given species. Compiled after values given for Manaus by Salati and Vose [27] and Leopolodo et al [28], we took the actual precipitation input of the year 2012, which differs only minimally from the original studies by Salati and Vose [27] and Leopolodo et al [28]. 2 Estimates derived from measurements conducted by this study.…”
Section: Sap Flux Properties and Conductivity Of The Xylemmentioning
confidence: 99%
“…Estimates for the Central Amazon for years with similar rainfall rates as during our study period assume that approximately 74.1% of the annual rainfall is evapotranspired [27], which would be 1487 mm for our study year. Assuming a significant increase of soil evaporation from 0% in the forest [27,28] to up to 15% of the annual rainfall in the plantation [30] and a reduced evaporation of rainfall interception due to reduced leaf area in the plantation, we estimated an annual evapotranspiration rate of 898 mm above the plantation (Figure 3). This means locally an up to 40% reduction of evapotranspiration through land use conversion to such small-holder plantations and that the runoff rate would be significantly increased.…”
Section: Stand Transpiration Rate and Impact On The Local Water Budgetmentioning
confidence: 99%